Estudo de cerâmicas avançadas para fins de blindagem balística - Souza, Diego Sarti de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The research involving new materials has always been considered as a differential in the development of a technology company. This occurred naturally since ancient times, often motivated by reasons of a certain age, where the most common material used was also the name of your time and may be cited as an example the Bronze Age, and later was the Iron. Currently, the use of firearms are they used in resolving conflicts between countries, or a more equivocal, as an instrument of social banditry make innovations in the area of shielding welcome, whether for personal use, in the form of vests or vehicle such as cars, tanks and even aircraft. In this context, is a Silicon Carbide Ceramic, with low density and high hardness. Thus, the aim of this study is the evaluation and comparison of these materials, seeking to improve their properties by means of additives such as boron and silicon metal and amorphous YAG. For this work, the specimens were pre-shaped by means of uniaxial later to be referred for isostatic pressing and sintering. The maximum percentage for each additive was 5%, except for the YAG whose percentage was 8.2% (mass percentage). All compositions were subjected to the same tests (x-ray diffraction, apparent density, optical microscopy, Vickers hardness, scanning electron Microscopita), so that one could draw a comparison between the materials under study, samples that showed better mechanical properties and micro structural, related here by hardness testing and microscopy (optical and SEM) were the silicon carbide doped with YAG and alumina samples, demonstrating the potential of these materials for ballistic protection. Other compositions have high porosity, which is highly undesirable, since in order to harmful influences on the mechanical properties discussed below

A pesquisa envolvendo novos materiais sempre foi considerada como um diferencial no desenvolvimento tecnológico e cultural de uma sociedade. Este fato ocorreu de forma natural desde a antiguidade, muitas vezes motivada por motivos de uma determinada época, onde o material mais comum utilizado também consistia no nome de seu tempo, podendo-se citar como exemplo a Era do Bronze, e posteriormente a Era do Ferro. Atualmente, a utilização de armas de fogo sejam elas utilizadas na resolução de conflitos entres países, ou de uma forma mais equívoca, na escalada da violência social tornam inovações na área de segurança e blindagem são bem-vindas, sejam elas de uso pessoal, na forma de coletes, ou veicular como carros, tanques e ainda aeronaves. É nesse contexto que se encontra a cerâmica de Carbeto de Silício, com baixa densidade e elevada dureza. Desta forma, o objetivo desse trabalho é a avaliação e comparação desses materiais, buscando o melhoramento de suas propriedades por meio de aditivos como boro amorfo e silício metálico e YAG. Para este trabalho, os corpos de prova foram pré-conformados por meio de prensagem uniaxial para posteriormente serem encaminhados para prensagem isostática e sinterização. O percentual máximo para cada aditivo foi de 5%, com exceção do YAG cujo percentual foi de 8,2%(percentuais em massa). BERNARDO ROCHA DE REZENDE (BERNARDINHO) Todas as composições foram submetidas aos mesmos ensaios (difração de raio-x, densidade de aparente, microscopia óptica, dureza Vickers, Microscopita Eletrônica de Varredura), de forma que se pudesse estabelecer uma comparação entre os materiais em estudo; As amostras que apresentaram melhores propriedades mecânicas e micro estruturais, relacionadas aqui pelo ensaio de dureza e microscopia(óptica e MEV) foram as de carbeto de silício aditivadas... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ceramica; Boro; Oxido de aluminio